Precipitation scavenging of aerosol particles at a rural site in the Czech Republic. Issue 1 (1st December 2016) - Zikova, Nadezda; Zdimal, Vladimir
Abstract : The influence of in-cloud and below-cloud scavenging, described by the obscurities (mist, fog and shallow fog) and precipitation, on submicron atmospheric aerosol (AA) particle number size distributions (PNSDs) was studied using 5 years of measurements at the rural background station Košetice. The typical PNSDs during individual meteorological phenomena were compared, and the change in the concentrations before and after the beginning of the phenomenon, the scavenging coefficient λ s, and the rate of change of the AA concentrations with time were computed. It was found that both obscurities and precipitation have a strong influence on the AA concentrations, both on the total number concentrations and on the PNSDs. The presence of phenomena even changes the number of modes on the PNSDs. The PNSD main mode is shifted to the larger particles, and the concentrations of particles smaller than 50 nm in diameter are considerably lower. In nucleation mode, however, wet scavenging does not seem to be the main process influencing the AA concentrations, although its considerable effect on the concentration was proved. During obscurities, there is a typical PNSD to which the PNSDs converge at any mist/fog/shallow fog event. The concentrations of AA particles smaller than 80 nm are lower than they are during periods without any phenomenon recorded, and the concentrations of the strongly prevailing accumulation mode are higher. During liquid precipitation, PNSDs are lower when compared to non-event periods. With larger droplets of the phenomenon, the position of the main mode of the bimodal PNSDs is shifted to the smaller particles. The process of gas-to-particle conversion takes place in the breaks from precipitation during a rain showers period. Precipitation containing frozen hydrometeors behaves differently from liquid precipitation. Concentrations of AA particles larger than 200 nm during precipitation containing solid particles do not differ from non-event cases, suggesting insignificant scavenging.